2015
DOI: 10.1371/journal.pone.0123050
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Excitation Propagation in the Rabbit Heart: Optical Mapping and Transmural Microelectrode Recordings

Abstract: BackgroundBecause of the optical features of heart tissue, optical and electrical action potentials are only moderately associated, especially when near-infrared dyes are used in optical mapping (OM) studies.ObjectiveBy simultaneously recording transmural electrical action potentials (APs) and optical action potentials (OAPs), we aimed to evaluate the contributions of both electrical and optical influences to the shape of the OAP upstroke.Methods and ResultsA standard glass microelectrode and OM, using an near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 28 publications
(74 reference statements)
1
18
0
Order By: Relevance
“…The techniques and procedures used for the simultaneous measurement of fluorescence and electrical signals from whole-heart preparations have been described previously (6,7). In brief, experiments were performed on rabbits (New Zealand White) weighing 3.9 5 0.2 kg (n ¼ 12).…”
Section: Generalmentioning
confidence: 99%
“…The techniques and procedures used for the simultaneous measurement of fluorescence and electrical signals from whole-heart preparations have been described previously (6,7). In brief, experiments were performed on rabbits (New Zealand White) weighing 3.9 5 0.2 kg (n ¼ 12).…”
Section: Generalmentioning
confidence: 99%
“…After observing that CAR decreased electrical signal conduction, in our next step, we extended our studies to evaluate possible changes in various AP parameters under stimulation originating from different locations. We have previously demonstrated that when pacing was initiated via the atrial, endocardial, and epicardial surfaces, the spread of electrical activity varied, creating different situations in the myocardium [19]. Atrial pacing allows evaluation of the spread of electrical activity via the atrioventricular (AV) node.…”
Section: Resultsmentioning
confidence: 99%
“…Heart. New Zealand white rabbits (n = 9) of either sex (~3 kg) were used, and the methods have been detailed previously [19]. Briefly, after intraperitoneal injection of xylazine (10 mg/kg) and heparin (1000 U/kg), intravenous injection of ketamine (10 mg/kg) was performed.…”
Section: Preparation Of the Rabbitmentioning
confidence: 99%
See 2 more Smart Citations